Age Stereotypes in the Workplace: Common Stereotypes, Moderators, and Future Research Directions - Posthuma, Richard A.; Campion, Michael A. (Journal of management, 2009)
The authors identify, analyze, and summarize prior research from 117 research articles and books that deal with age stereotypes in the workplace. They discover and report the most prevalent and well-supported findings that have implications for human resource management. These findings are described in terms of prevalent age stereotypes that occur in work settings, evidence refuting age stereotypes, and moderators of age stereotypes. The authors provide recommendations for practice and future research.